2023
DOI: 10.15244/pjoes/154741
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Contribution of Climate Change and Human Activities to Runoff Changes in the Source Region of the Yellow River

Abstract: Assessing the characteristics of runoff changes and quantifying the contribution of influencing factors to runoff changes are crucial for water resources management and sustainable development in the source region of the Yellow River (SRYR). The intra-annual distribution of runoff depicted a double-peak effect. The first runoff peak in July was primarily influenced by precipitation, which did not completely flow after falling to the ground. However, some water was stored in the active layer of permafrost and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The highest maximum runoff value was from the Chern River Basin Part 1. In addition, it was found that the highest occurrence of runoff happened in two periods, September (dry season-flood season) and October (flood season-dry season) of every land use year in all three river basins, as previously reported [43,[55][56][57]. Therefore, it can be concluded that recent land use changes under the highest annual rainfall will cause the basin's highest runoff.…”
Section: Effects Of Land Use Changes On Runoff Volumesupporting
confidence: 72%
“…The highest maximum runoff value was from the Chern River Basin Part 1. In addition, it was found that the highest occurrence of runoff happened in two periods, September (dry season-flood season) and October (flood season-dry season) of every land use year in all three river basins, as previously reported [43,[55][56][57]. Therefore, it can be concluded that recent land use changes under the highest annual rainfall will cause the basin's highest runoff.…”
Section: Effects Of Land Use Changes On Runoff Volumesupporting
confidence: 72%
“…This study utilized three RCP scenarios (RCP2.6, RCP4.5, and RCP8.5) representing low, medium, and high socioeconomic developments. These three scenarios have been widely employed in numerous studies assessing the impacts of climate change [3,38]. Four GCMs (i.e., BCC-CSM1-1, CSIRO_MK3.6, HaDGEM2-ES, and NorESM1-M) were chosen depending on the previous literature to reduce the uncertainty in projected climate data.…”
Section: Representive Concentration Pathways Scenariosmentioning
confidence: 99%
“…Water is fluid and stored in different slope units such as mountains, forests, fields, lakes, grasslands, and sands in the basin, and the location, flow, and quality of these waters are deeply affected by climate change and human activities [15][16][17]. The water yield process of the basin slope under natural conditions is taken as the base scenario, the water yield process under climate change is used as the prediction scenario, and the water yield process under the disturbance of human activities is used as the comparison scenario, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%